1.5 for each friend, plus who eats fruit bars xD
1/3= 5/15
2/5= 6/15
5/15 + 6/15 = 11/15
15/15 - 11/15 = 4/15
Part C= 4/15
![f(x) = \sqrt{x + 2}](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%20%5Csqrt%7Bx%20%2B%202%7D%20%20)
What's The Fixed Point? Well, Let's Assume X=0, this is our point.
![f(0) = \sqrt{0 + 2} \\ f(0) = \sqrt{2} \\ this \: is \: our \: fixed \: point \: \\ (0, \sqrt{2} )](https://tex.z-dn.net/?f=f%280%29%20%3D%20%20%5Csqrt%7B0%20%2B%202%7D%20%20%5C%5C%20f%280%29%20%3D%20%20%5Csqrt%7B2%7D%20%20%5C%5C%20this%20%5C%3A%20is%20%5C%3A%20our%20%5C%3A%20fixed%20%5C%3A%20point%20%5C%3A%20%20%5C%5C%20%280%2C%20%5Csqrt%7B2%7D%20%29)
OR
![f(p) = \sqrt{p + 2} \\ \\ or \: \sqrt{x + 2} = 0 \\ ( \sqrt{x + 2} ) ^{2} = {0}^{2} \\ x + 2 = 0 \\ x = - 2](https://tex.z-dn.net/?f=f%28p%29%20%3D%20%20%5Csqrt%7Bp%20%2B%202%7D%20%20%5C%5C%20%20%5C%5C%20%20or%20%5C%3A%20%20%5Csqrt%7Bx%20%2B%202%7D%20%20%3D%200%20%5C%5C%20%28%20%5Csqrt%7Bx%20%2B%202%7D%20%29%20%5E%7B2%7D%20%20%3D%20%20%7B0%7D%5E%7B2%7D%20%20%5C%5C%20x%20%2B%202%20%3D%200%20%5C%5C%20x%20%20%3D%20%20-%202)
I'm unaware of the nature of the question, so here are some different ways a fixed point is found based on the merits of the question.
Answer: Part A is 2 and 6 Part B is 2
Step-by-step explanation:
Part A: Here is the explanation. So, you started at with the expression 3x^2+8x+4 and when you're are factoring, you have 3x^2+px+pq+4. You can substitute the p and q for 6 and 2. What they did is they replaced 8x with px+qx. To get 8x, p needs to be 6 and q needs to be 2, or the other way around. TIP: The numbers just have to add up to 8 on this one. It doesn't have to be 6 and 2.
Part B: Here is what I got so far... 3x(x+r) is 3x^2+3xr. Also, s(x+r) is sx+sr. The equation becomes, 3x^2+3xr+sx+sr. R can be 2 and s can be 2. Here is my reasoning: The original expression was 3x^2+8x+4. We already have the 3x^2, so now we need to find what the others are by determining what r and s equal. R and s can both be 2 to make four. 2x2 is 4. Let's see if it can make 8. 3xr becomes 6x and sx becomes 2x. 6x+2x is 8x.
It would be: a = v₂-v₁ / t
a = (70-10) / 12
a = 60 / 12
a = 5 m/s²
So, option A is your final answer.
Hope this helps!